Pakistan : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper assesses Pakistan's Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criterion. Developments in the first months of 2002 indicate further progress toward the program's macroeconomic objectives. Progress on the structural front was broadly in line with the program, in particular in the area of tax administration, fiscal transparency, and privatization. All but one of the performance criteria for end-March 2002 were met. The authorities request a waiver for the nonobservance of the performance criterion on Central Board of Revenue (CBR) revenue.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet